In-section Click-iT detection and super-resolution CLEM analysis of nucleolar ultrastructure and replication in plants - Franek, Michal; Koptašíková, Lenka; Mikšátko, Jíří; Liebl, David; Macíčková, Eliška; Pospíšil, Jakub; Esner, Milan; Dvořáčková, Martina; Fajkus, Jíří (Nature communications, 2024)
Correlative light and electron microscopy (CLEM) is an important tool for the localisation of target molecule(s) and their spatial correlation with the ultrastructural map of subcellular features at the nanometre scale. Adoption of these advanced imaging methods has been limited in plant biology, due to challenges with plant tissue permeability, fluorescence labelling efficiency, indexing of features of interest throughout the complex 3D volume and their re-localization on micrographs of ultrathin cross-sections. Here, we demonstrate an imaging approach based on tissue processing and embedding into methacrylate resin followed by imaging of sections by both, single-molecule localization microscopy and transmission electron microscopy using consecutive CLEM and same-section CLEM correlative workflow. Importantly, we demonstrate that the use of a particular type of embedding resin is not only compatible with single-molecule localization microscopy but shows improvements in the fluorophore blinking behavior relative to the whole-mount approaches. Here, we use a commercially available Click-iT ethynyl-deoxyuridine cell proliferation kit to visualize the DNA replication sites of wild-type Arabidopsis thaliana seedlings, as well as fasciata1 and nucleolin1 plants and apply our in-section CLEM imaging workflow for the analysis of S-phase progression and nucleolar organization in mutant plants with aberrant nucleolar phenotypes.
Keywords: Microscopy, Electron; elektrony; transmisní elektronová mikroskopie; fluorescenční mikroskopie; Microscopy, Fluorescence; Single Molecule Imaging; zobrazení jednotlivé molekuly; Microscopy, Electron, Transmission; Arabidopsis; Electrons; elektronová mikroskopie